Good Corporate Governance dalam Agresivitas Pajak pada Perusahaan Pertambangan di Bursa Efek Indonesia - Desta Adelia Putri; Hwihanus Hwihanus (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to determine the relationship between leverage, company characteristics, and financial performance with illegal tax aggressiveness in mining companies listed on the Indonesia Stock Exchange in 2019-2022. The research method used is quantitative with secondary data. The population of this study are mining sector companies listed on the Indonesia Stock Exchange in 2019-2022. The sample obtained was 10 companies using purposive sampling method. Data analysis using SmartPLS. The results showed that leverage, company characteristics, and financial performance had no significant effect on tax aggressiveness. This means that mining companies that have high leverage, poor company characteristics, and poor financial performance do not tend to practice tax aggressiveness. In addition, good corporate governance cannot moderate the relationship between leverage, company characteristics and financial performance with tax aggressiveness. This means that leverage, company characteristics and financial performance still have a significant influence on tax aggressiveness, even though the company has good corporate governance.